THE RELATIONSHIP BETWEEN LEARNING MOTIVATION, LEARNING ENVIRONMENT AND LEARNING INTENSITY WITH MATHEMATICS LEARNING OUTCOMES - Ari Purwanti; Edi Prajitno (Universitas Ahmad Dahlan, 2019)
Low students' learning outcomes are related to many factors. Learning motivation, learning environment at home, and learning intensity are among them. This study aims to determine whether there are positive and significant relations between learning motivation, learning environment at home, and learning intensity and mathematics learning outcomes of grade VIII students of SMP Muhammadiyah 2 Yogyakarta in the even semester academic year of 2016/2017. This study's population were grade VIII students of Junior High School (SMP) Muhammadiyah 2 Yogyakarta in the academic year of 2016/2017, consisting of grade VIII students class G and H with a total number of 66 students. A random sampling technique was applied to take the sample of this research, which is grade VIII students class G. The data on learning motivation, learning environment at home, and learning intensity were obtained through questionnaires. At the same time, the data of the mathematics learning outcomes were obtained through the test. The research instruments were tested using a validity test, differential test, and reliability test. Analysis prerequisite tests include normality, linearity, and independence test. Product moment and multiple linear regression analysis were used to analyze the data. The results show positive and significant relations between learning motivation, learning environment at home, learning intensity, and mathematics learning outcomes of grade VIII students of SMP Muhammadiyah 2 Yogyakarta in the even semester of the academic year of 2016/2017. The results are evident in which is 4.8 > 2.9 with R = 0,6 dan R2 = 0,3 with , with RC = 55,7%, RC = 23,3% and RC EC %, EC and EC = 6,8%.